Neopestalotiopsis zimbabwana Isolated from Xylaria Stromata - Rudy Hermawan; Rena Rifki Safitri; Muhamad Raffel Sidiq (Biotropika: Journal of Tropical Biology, 2021)
Neopestalotiopsis is one of pestalotioid fungi. Neopestalotiopsis has versicolourous in the third cell (median cell). This genus is identified as pathogenic and endophytic fungi in the plant. Neopestalotiopsis strain X1 was isolated from Xylaria stromata assumed as endophytic fungi. The surface sterilization was conducted, then isolated into PDA (1/2 receipt of potato dextrose). The morphology was observed in a fresh PDA medium. Genomic DNA was extracted and amplified for the Large Subunit region. A phylogenetic tree was built using RAxML Black Box. The morphology showed that the five cells in a conidium were an appearance with the black color of the septate in the third cell (median cell). The appendage on the basal cell was only a single tubular appendage. The appendage on the apical was two until three tubular appendages. The phylogenetic tree showed that Neopestalotiopsis strain X1 was Neopestalotiopsis zimbabwana. The sequence was deposited into GenBank as MW422813. This study was the first report for Neopestalotiopsis species isolated from micro-mushroom (Xylaria stromata).